Studi Kasus: Sistem Informasi dan Pelayanan Administrasi Kependudukan - Mifthul Huda; Slamet Wiyono; M. Fikri Hidayatullah; Saeful Bahri (Komputika : Jurnal Sistem Komputer, 2020)
Sidamulya Village is an administrative area in the Warureja sub-district of Tegal district, Central Java province. Sidamulya village as a village far from the center of government cannot be separated from the village problems that commonly occur. The problem that occurs in these village is that there are often complaints from the community regarding population administration services that consume a lot of time and village information that is not spread to the community. Information system and population administration services are made to solve existing problems. This article explains how the making and testing of system of population administration and information services web-based. The method used in making the system was the waterfall method. The information system created has several facilities, namely; the Home menu, the Village Profile menu, the Information menu, and the Service menu. Testing the system uses two methods, namely; white-box testing and black-box testing methods. White-box test results indicate that an error has not been found on the system. Black-box test results indicate that the system have running in accordance with its functionality.